2018
DOI: 10.1097/01.ogx.0000527998.76392.af
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Peripartum Perinatal Mortality in Unplanned Births Outside an Institution: A Retrospective Population-Based Study

Abstract: BACKGROUND: Births in midwife-led institutions may reduce the frequency of medical interventions and provide cost-effective care, while larger institutions offer medically and technically advanced obstetric care. Unplanned births outside an institution and intrapartum stillbirths have frequently been excluded in previous studies on adverse outcomes by place of birth. OBJECTIVE: The objective of the study was to assess peripartum mortality by place of birth and travel time to obstetric institutions, with the hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 17 publications
1
13
1
2
Order By: Relevance
“…Deaths during the neonatal period may be due to a combination of factors including fetal medical conditions, maternal medical and sociodemographic conditions and lack of monitoring and interventions during pregnancy, labor and after birth. Some previous studies have shown associations between increasing travel time and out-of-hospital birth 3,14,17,28 and subsequent risk of infant mortality, 3,14,15,17,29 whereas others have not. 18,19 It's possible that reports from less recent studies, including births from the 1950s to the early 1990s, that increasing travel time did not change the outcome of infant death, 18,19 could be due to the fact that the available quality of care of newborns at the time did not contribute to significant reductions of infant mortality overall, as in present times.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Deaths during the neonatal period may be due to a combination of factors including fetal medical conditions, maternal medical and sociodemographic conditions and lack of monitoring and interventions during pregnancy, labor and after birth. Some previous studies have shown associations between increasing travel time and out-of-hospital birth 3,14,17,28 and subsequent risk of infant mortality, 3,14,15,17,29 whereas others have not. 18,19 It's possible that reports from less recent studies, including births from the 1950s to the early 1990s, that increasing travel time did not change the outcome of infant death, 18,19 could be due to the fact that the available quality of care of newborns at the time did not contribute to significant reductions of infant mortality overall, as in present times.…”
Section: Discussionmentioning
confidence: 95%
“…The Norwegian study created travel zones through GIS analyses based on coordinates for registered home addresses and the nearest delivery unit within a given time limit. 14 The proportion of individuals >2 hours from the nearest delivery unit in Norway was 0.9%, and unplanned out-ofhospital birth 0.7%. These numbers are very similar to those found in our study (1% and 0.6%, respectively).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations